Work inequalities in the crisis: evidence from Europe (Geneva, 2011)
"Work inequalities in the crisis provides an in-depth overview of the effects of the crisis on inequalities in the world of work. It examines these inequalities multi-dimensionally, looking at employment, wages and incomes, working conditions and social dialogue. At the same time, it investigates whether the crisis may halt the progress made in Europe towards better quality jobs and working conditions.